Bilateral primary psoas abscesses due to methicillin-resistant Staphylococcus aureus in a neutropenic patient: a case report. (December 2016) - Bakri, Faris; Hadidy, Azmy; Hadidi, Fadi; Ryalat, Nosaiba; Saket, Lina; Shurbasi, Nour; Melhem, Jamal
Abstract Background Pyogenic abscess of psoas muscles is a rare condition. Psoas abscess due to methicillin-resistantStaphylococcus aureus is an emerging and rare infection and so far the related data are scarce. Case presentation We report the rare case of primary and bilateral large psoas abscesses due to methicillin-resistantStaphylococcus aureus in a 54-year-old Arab Jordanian woman with breast cancer who had neutropenia after starting chemotherapy. She was diagnosed 50 days after onset of symptoms. However, despite this delay in diagnosis and the large size of the abscesses, she had a full recovery. She was treated with antibiotics and percutaneous drainage and was doing very well at a follow up of 18 months. Conclusions Psoas abscess due to methicillin-resistantStaphylococcus aureus might have insidious presentation with extensive disease especially in immunocompromised patients. However, it can be managed effectively with percutaneous catheter drainage and appropriate antibiotic therapy.